Perundang-Undangan Rumah Sakit Dalam Pengelolaan Limbah Medis Sebagai Upaya Memantapkan Tanggung Jawab Lingkungan - I Gede Perdana Yoga (Program Studi Teknik Lingkungan Unmas Denpasar, 2023)
Hospital medical waste is part of the hospital's environmental sanitation activities, which aims to protect the public from the dangers of environmental pollution caused by hospital waste and prevent the spread of disease. The purpose of this research is to find out the regulations or legal principles of medical waste management in hospitals. This type of research relates to normative laws and regulations, research materials consist of primary and secondary materials. Data were obtained using a qualitative descriptive method. Based on the results of the study, hospital waste management policies can be implemented in several ways, namely volume reduction, reuse, recycling and elimination of manipulation in accordance with laws and regulations.